Horizontal Stress Control In Underground Coal Mines (1dbd7295-90f8-4003-a003-9120dc19934c) - S. M. Matthews (International Conference on Ground Control in Mining, 1992)
The magnitude and orientation of the in situ stressfield has been determined as a key factor in controlling the stability of openings for both coal mine development and extraction. Monitoring of roadway and pillar behaviour in conjunction with numerical analysis has identified specific stress control measures that have been successfully applied to improve productivity in underground coal mining operations. The influence of the major horizontal stressfield on the stability of openings has been identified at a wide range of sites including mines in Australia, Britain, the USA, New Zealand and Japan. Stress mapping, stress measurement and stress monitoring techniques have been applied to define the in situ stress regime and, together with the correlation of measurements of rock deformation and rock reinforcement behaviour, has enabled appropriate stress control measures to be developed. Stress control measures for development headings have required the selection of roadway orientation, roadway sequencing, reinforcement density and pillar size. The monitoring of behaviour at a range of trial sites has confirmed significant improvements in development stability. Stress control measures for longwall extraction have required rational selection of longwall orientation and extraction direction. Where a mine layout design incorporating the optimum longwall layout design has not been possible, the use of sacrificial roadways has been successfully applied to protect key roadways from stress concentration effects. Comprehensive in situ monitoring of behaviour has been carried out to confirm the mechanisms involved.